2016
DOI: 10.5935/1678-9741.20160001
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease and Impacts on Child Development

Abstract: Objective:To evaluate the child development and evaluate a possible association with the commitment by biopsychosocial factors of children with and without congenital heart disease.Methods:Observational study of case-control with three groups: Group 1 - children with congenital heart disease without surgical correction; Group 2 - children with congenital heart disease who underwent surgery; and Group 3 - healthy children. Children were assessed by socio-demographic and clinical questionnaire and the Denver II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
0
16
0
5
Order By: Relevance
“…In our study, the cyanotic showed the poor quality of life than acyanotic heart disease children; it supposed to be related to the difference in cognitive and nutritional status. Therefore, a multidisciplinary approach should be applied for early identification of those impairments to offer the best opportunity for treatment that may allow the child to reach the fullest potential in adulthood and minimize the negative impact on the quality of life and parents should be more aware and responsive to the development and nutrition aspect of their child [27].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the cyanotic showed the poor quality of life than acyanotic heart disease children; it supposed to be related to the difference in cognitive and nutritional status. Therefore, a multidisciplinary approach should be applied for early identification of those impairments to offer the best opportunity for treatment that may allow the child to reach the fullest potential in adulthood and minimize the negative impact on the quality of life and parents should be more aware and responsive to the development and nutrition aspect of their child [27].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital heart disease (CHD) represents a public health issue due to its high incidence of 9/1000 live births . Undernutrition may occur in up to 90% of these patients and may be related to poorer surgical and neurological outcomes . Nutrition recovery may take several months to occur after surgery, and there is evidence that these children may not recover stature, remaining shorter in height than expected…”
Section: Introductionmentioning
confidence: 99%
“…1 Undernutrition may occur in up to 90% of these patients 2 and may be related to poorer surgical and neurological outcomes. 3,4 Nutrition recovery may take several months to occur after surgery, and there is evidence that these children may not recover stature, remaining shorter in height than expected. 5 The complexity of this group of patients often causes insecurity when beginning the diet and also frequent interruptions in feeding, which will contribute to a lower energy supply.…”
Section: Introductionmentioning
confidence: 99%
“…Las intervenciones en rehabilitación cardiaca pueden minimizar los efectos negativos a nivel motor y en la capacidad funcional, al igual que fomentar y hacer que el ambiente del infante o del adolescente sea favorable al desarrollo de sus habilidades. (Mari, Cascudo, & Alchieri , 2016)…”
Section: Rehabilitación Cardiaca En El Infante Y Adolescente Con Cardunclassified